2021
DOI: 10.1093/rb/rbab070
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-4 functionalization of tissue regeneration scaffolds improves interaction with endothelial progenitor cells

Abstract: Key to most implanted cell free scaffolds for tissue regeneration is the ability to sequester and retain undifferentiated mesenchymal stem cells at the repair site. In this report, syndecan-4, a heparan sulfate containing proteoglycan, was investigated as a unique molecule for use in scaffold functionalization. An electrospun hybrid scaffold comprised of poly (glycerol) sebacate (PGS), silk fibroin and type I collagen (PFC) was used as a model scaffold to develop a procedure and test the hypothesis that functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…22 We have also found in a previous study that syndecan-4 and SDF-1α functionalized PFC (fPFC) significantly facilitated the binding of ECFCs compared with syndecan-4 fPFC, SDF-1α fPFC or non-fPFC. 25 In the current study, we confirmed and extended these findings to demonstrate more extensive cell spreading and differentiation of ECFCs if PFC was functionalized with syndecan-4 and SDF-1α. While only SDF-1α was the exogenous growth factor used, the presence of syndecan-4 on PFC may facilitate growth, spreading, and differentiation of ECFCs in multiple and versatile ways (see Figure 1).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…22 We have also found in a previous study that syndecan-4 and SDF-1α functionalized PFC (fPFC) significantly facilitated the binding of ECFCs compared with syndecan-4 fPFC, SDF-1α fPFC or non-fPFC. 25 In the current study, we confirmed and extended these findings to demonstrate more extensive cell spreading and differentiation of ECFCs if PFC was functionalized with syndecan-4 and SDF-1α. While only SDF-1α was the exogenous growth factor used, the presence of syndecan-4 on PFC may facilitate growth, spreading, and differentiation of ECFCs in multiple and versatile ways (see Figure 1).…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have shown that PFC is compositionally and mechanically similar to native vascular tissue and supports endothelial cell growth in culture 22 . We have also found in a previous study that syndecan‐4 and SDF‐1α functionalized PFC (fPFC) significantly facilitated the binding of ECFCs compared with syndecan‐4 fPFC, SDF‐1α fPFC or non‐fPFC 25 . In the current study, we confirmed and extended these findings to demonstrate more extensive cell spreading and differentiation of ECFCs if PFC was functionalized with syndecan‐4 and SDF‐1α.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The extracellular signals are transduced via the cytoskeleton to regulate transcription in nuclei, resulting in the change of cell behaviors such as adhesion, migration, differentiation, and so forth, which is known as mechanotransduction . Mechanotransduction is influenced by cell–material interactions and its insight is helpful for the design of biomedical materials. …”
Section: Introductionmentioning
confidence: 99%